Analisis Distribusi Hasil Tangkapan Berdasarkan Aktivitas Pasar dan Pemasaran Pelabuhan Perikanan Jawa Tengah - Andi Perdana Gumilang (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2021)
The fishing port has a function as a place for marketing and distribution of fish. Along with the increasing demand for fishery commodities, it is necessary to study the distribution of catches for the realization of the capture fisheries business. This study aims to examine the marketing distribution of catches at fishing ports in Central Java based on market aspects and marketing actors. The research method is a survey method by observing and assessing factors related to the marketing distribution of the catch. The analysis was carried out in a comparative descriptive manner through the presentation of distribution maps and tables. The results showed that the distribution of catches on the north coast of Central Java based on market aspects includes local and regional markets. Distribution of catches based on marketing actors found three patterns. The first pattern of distribution is from fishermen to the Fish Auction Place (TPI) then the collectors/basket traders continue to wholesalers, retailers and consumers. The second pattern is almost the same as the first pattern, except that fish from collectors after being processed or preserved is then continued to retailers and then sold to consumers. The third pattern is the catch from fishermen directly to retailers and then to consumers.